Analisis perceived organizational support dan budaya kerja terhadap beban kerja dalam meningkatkan kinerja karyawan bank menuju new normal - Honorata Ratnawati Dwi Putranti; Dian Al Ardhi Mahalalita (STIE Perbanas Surabaya, 2021)
The Covid 19 pandemic—which has spread throughout the world since early 2020— has had an impact on several countries, including Indonesia. This condition changes the company's policy, intended to maintain optimal employee performance. This study aims to determine the effect of perceived organizational support (POS) and work culture on employee performance. The population of this study were 179 employees of Bank BTN Semarang branch with a sample of 65. The sample was taken using a stratified random sampling with primary data distributed by online questionnaires. The results showed that POS has a significant effect on performance, work culture has a positive and significant effect on performance, POS has a negative and significant effect on workload, Work culture has a negative and significant effect on workload and workload has a negative and insignificant effect on performance significantly influence workload, workload does not significantly influence employee performance and work culture. Work culture has a significant effect on employee performance. POS has a significant effect on workload, work culture has a significant direct effect and a significant indirect effect. POS has a significant direct and indirect effect. The study is useful for understanding how to optimize company management and creating a work culture in improving the performance of bank employees.